LDLR promotes autophagy‐mediated cisplatin resistance in ovarian cancer associated with the PI3K/AKT/mTOR signaling pathway - Lei Liu; Yu‐Hui Sun; Ran An; Rong‐Jie Cheng; Nan Li; Jian‐Hua Zheng (Kaohsiung Journal of Medical Sciences, 2023)
Abstract Autophagy is one of the underlying causes of resistance to many antitumor drugs, including cisplatin (DDP). The low‐density lipoprotein receptor (LDLR) is a regulator of ovarian cancer (OC) progression. However, whether LDLR regulates DDP resistance in OC via autophagy‐related pathways remains unclear. LDLR expression was measured by quantitative real‐time PCR, western blot (WB) and IHC staining. A Cell Counting Kit 8 assay was employed to evaluate DDP resistance and cell viability, and flow cytometry was used to assess apoptosis. WB analysis was employed to evaluate the expression of autophagy‐related proteins and PI3K/AKT/mTOR signaling pathway proteins. The autophagolysosomes and the fluorescence intensity of LC3 were observed by transmission electron microscopy and immunofluorescence staining, respectively. A xenograft tumor model was established to explore the role of LDLR in vivo. LDLR was highly expressed in OC cells, which was correlated with disease progression. In DDP‐resistant OC cells, high LDLR expression was related to DDP resistance and autophagy. Downregulation of LDLR repressed autophagy and growth in DDP‐resistant OC cell lines by activating the PI3K/AKT/mTOR pathway, and these effects were eliminated by an mTOR inhibitor. In addition, LDLR knockdown also reduced OC tumor growth by suppressing autophagy associated with the PI3K/AKT/mTOR pathway. LDLR promoted autophagy‐mediated DDP resistance in OC associated with the PI3K/AKT/mTOR pathway, indicating that LDLR might be a new target to prevent DDP resistance in OC patients.